2020
DOI: 10.3390/molecules25173921
|View full text |Cite
|
Sign up to set email alerts
|

Improved Extraction Efficiency of Antioxidant Bioactive Compounds from Tetraselmis chuii and Phaedoactylum tricornutum Using Pulsed Electric Fields

Abstract: Pulsed electric fields (PEF) is a promising technology that allows the selective extraction of high-added value compounds by electroporation. Thus, PEF provides numerous opportunities for the energy efficient isolation of valuable microalgal bioactive substances (i.e., pigments and polyphenols). The efficiency of PEF-assisted extraction combined with aqueous or dimethyl sulfoxide (DMSO) solvents in recovering pigments and polyphenols from microalgae Tetraselmis chuii (T. chuii) and Phaeodactylum tricornutum (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 38 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…The differences with our study can be explained regarding the huge time interval. For instance, in the present study, a time range was established from 0.5 min up to 30 min, while in the study conducted by Kokkali et al [15], the time range was from 4 h to 24 h. Figure 5. Influence of the different extraction conditions (A) and main effects chart for these conditions (B) on the total phenolic compounds (TPC) recovery yield (mg/100 g dry matter).…”
Section: Antioxidant Capacity and Compoundsmentioning
confidence: 43%
See 2 more Smart Citations
“…The differences with our study can be explained regarding the huge time interval. For instance, in the present study, a time range was established from 0.5 min up to 30 min, while in the study conducted by Kokkali et al [15], the time range was from 4 h to 24 h. Figure 5. Influence of the different extraction conditions (A) and main effects chart for these conditions (B) on the total phenolic compounds (TPC) recovery yield (mg/100 g dry matter).…”
Section: Antioxidant Capacity and Compoundsmentioning
confidence: 43%
“…Akyıl et al [34] also found a significant influence of the extraction time on the antioxidant activity, measured by DPPH, when they optimized the bioactive compound extraction from P. tricornutum. However, Kokkali et al [15] found a minimal decrease in antioxidant activity, measured by ABTS in P. tricornutum aqueous extracts, comparing 4 h and 24 h of extraction. The differences with our study can be explained regarding the huge time interval.…”
Section: Antioxidant Capacity and Compoundsmentioning
confidence: 96%
See 1 more Smart Citation
“…Two experiments were performed, in line with Lohani et al [ 21 ], the first one with a specific energy input of 100 kJ/kg and the second one of 17 kJ/kg; the number of pulses was 115 and 9 pulses, depending on the voltage applied (field strength 2 or 3 kV/cm, respectively). These conditions were derived from the fact that a minimum of 1 kV/cm field strength is required to produce changes in cells and 3–4 kV/cm for the electroporation [ 29 ]. For this reason, only two experiments were carried out in order to compare a treatment of moderate intensity and short duration (3 kV/cm and 9 pulses with an energy per pulse of 450 J) with another one of low intensity and long duration (2 kV/cm and 100 pulses with an energy per pulse of 200 J).…”
Section: Methodsmentioning
confidence: 99%
“…According to a recent report by the Food and Agriculture Organization of the United Nations (FAO), world fish production increased from 19 million metric tons (MMT) in 1950 to 171 MMT in 2016 [24]. In per capita terms, fish consumption has also risen from 9.0 kg in 1961 to 20.2 kg in 2015 [25]. As a consequence of industrial fish processing, a great amount of waste is generated each year, which can represent up to 75% of the total weight of the catch, although it differs according to the species, size, or the processing type [26].…”
Section: Current Status Of Consumption Of Aquatic Products and Utilizmentioning
confidence: 99%